Preservation of organ function in locally advanced non-metastatic Gastrointestinal Stromal Tumors (GIST) of the stomach by neoadjuvant imatinib therapy - Vassos, Nikolaos; Jakob, Jens; Kähler, Georg; Reichardt, Peter; Marx, Alexander; Dimitrakopoulou-Strauss, Antonia; Rathmann, Nils-Andreas; Wardelmann, Eva; Hohenberger, Peter (Cancers, 2021)
Background: Neoadjuvant imatinib mesylate (IM) for advanced, non-metastatic gastrointestinal stromal tumors (GIST) of stomach is recommended to downsize the tumor prompting less-extensive operations and preservation of organ function. Methods: We analyzed the clinical-histopathological profile and oncological outcome of 55 patients (median age 58.2 years; range, 30-86 years) with biopsy-proven, cM0, gastric GIST who underwent IM therapy followed by surgery with a median follow-up of 82 months. Results: Initial median tumor size was 113 mm (range, 65-330 mm) and 10 patients started with acute upper GI bleeding. After a median 10 months (range, 2-21 months) of treatment, tumor size had shrunk to 62 mm (range, 22-200 mm). According to Response Evaluation Criteria In Solid Tumors version 1.0 and version 1.1 (RECIST 1.1), 39 (75%) patients had partial response and 14 patients had stable disease, with no progressive disease. At plateau response, 50 patients underwent surgery with an R0 resection rate of 94% and pathological complete response in 24%. In 12 cases (24%), downstaging allowed laparoscopic resection. The mean recurrence-free survival (RFS) was 123 months (95%CI; 99-147) and the estimated 5-year RFS was 84%. Conclusions: Neoadjuvant IM allowed stomach preservation in 96% of our patients with excellent long-term RFS, even when starting treatment during an episode of upper GI bleeding. Preservation of the stomach provides the physiological basis for the use of oral IM in the adjuvant or metastatic setting.
Gesehen am 07.07.2021